IMPLEMENTASI UNDANG-UNDANG NOMOR 6 TAHUN 2014 KEPALA DESA DALAM MENJALANKAN TUGAS DI DESA AUR KUNING KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR - eka, eka (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2019)
This study examines the task of village heads in carrying out their duties in Aur Kuning Village, Kampar Kiri Hulu Subdistrict, as agreed in the Regulation of the Minister of State for Administrative Reform Number: 13 of 2009 concerning Guidelines for Improving the Quality of Public Services, Rights, Duties and Obligations of Village Heads in accordance with the provisions of Law Number 6 of 2014 concerning Villages. Article 26 The Village Head who organizes the Village Government, implements Village Development, Village community development, and empoweres the Village community. The design of this study uses a qualitative descriptive method that will discuss and review secondary data related to documents relating to the Village Head in the Task Process in Aur Kuning Village, Kampar Kiri Hulu Subdistrict. In addition, so that the research objectives can involve researchers also using primary data as a result of interviews with research informants, namely: Village Chief Aur Kuning, Secretary of Desa Aur Kuning, Village Staff of Aur Kuning and Community of Desa Aur Kuning. The Village Head in Aur Kuning Village, Kampar Kiri District has been effective in the context of development. His job was as the head of Aur Kuning Village, Kampar Kiri District